2001
DOI: 10.1177/0148607101025006299
|View full text |Cite
|
Sign up to set email alerts
|

Early Enteral Nutrition in Critically III Patients With a High‐Protein Diet Enriched with Arginine, Fiber, and Antioxidants Compared With a Standard High‐Protein Diet. The Effect on Nosocomial Infections and Outcome

Abstract: Critically ill patients fed a high-protein diet enriched with arginine, fiber, and antioxidants had a significantly lower catheter-related sepsis rate than patients fed a standard high-protein diet. There were no differences in mortality or ICU and hospital length of stay. The subgroup of patients fed the study diet for >2 days showed a trend toward decreased mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 50 publications
1
94
0
4
Order By: Relevance
“…Higher albumin serum was demonstrated in the enriched formula group compared with standard formula. Caparros et al (2001) showed in critically ill patients with a diet enriched with arginine and fiber, a decrease in catheter-related sepsis rate. In our study with better nourished patients than those reported in previous studies, no differences were detected in postoperative infection complications, but wound complications were lower and plasma proteins improved with standard and immune-enhancing formula; we do not have a Arginine stimulates anabolic hormone release, improves survival in gut-derived sepsis and peritonitis by modulating bacterial clearance, and has been demonstrated to enhance natural killer cell cytotoxicity, increase T-cell proliferation, and accelerate wound healing (Reynolds et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher albumin serum was demonstrated in the enriched formula group compared with standard formula. Caparros et al (2001) showed in critically ill patients with a diet enriched with arginine and fiber, a decrease in catheter-related sepsis rate. In our study with better nourished patients than those reported in previous studies, no differences were detected in postoperative infection complications, but wound complications were lower and plasma proteins improved with standard and immune-enhancing formula; we do not have a Arginine stimulates anabolic hormone release, improves survival in gut-derived sepsis and peritonitis by modulating bacterial clearance, and has been demonstrated to enhance natural killer cell cytotoxicity, increase T-cell proliferation, and accelerate wound healing (Reynolds et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Although immune dysfunction could be multifactorial, the immune system may be modulated by specific nutritional substrates, such as arginine (Daly et al, 1998). There is evidence suggesting that enteral nutrition, supplemented with different agents including arginine and dietary fiber, improves immune function and reduces postoperative complications, in different groups of patients, such as those undergoing pancreatic surgery , surgery for stomach and colo-rectum cancer (Gianoti et al, 1999;Wu et al, 2001), and critically ill patients (Caparros et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…There were no differences in mortality or ICU and hospital length of stay 13 . Another study suggests that postoperative enteral nutrition with supplemental Arg, RNA, and omega-3 fatty acids instead of a standard enteral diet significantly improved immunologic, metabolic, and clinical outcomes in patients with upper gastrointestinal malignancies who were undergoing major elective surgery 14 .…”
Section: Essentialmentioning
confidence: 74%
“…Efron et al 9 Enhancing wound healing, regulating endocrine activity and potentiating immune activity Wu et al 8 Beneficial in improving reproductive, cardiovascular, pulmonary, renal, gastrointestinal, liver and immune functions, as well as facilitating wound healing, enhancing insulin sensitivity, and maintaining tissue integrity Daly et al 12 Enhancing or preserving immune function in high-risk surgical patients and theoretically improving the host's capacity to resist infection Caparrós et al 13 Significantly lower catheter-related sepsis rate…”
Section: Author Effect Of Supplementationmentioning
confidence: 99%
“…Other studies have shown that arginine increased lymphocytic interleukin-2 production and augmented lysis of tumours by macrophages . There is evidence suggesting that enteral nutrition, supplemented with different agents including arginine and dietary fibre, improves immune function and reduces postoperative complications, in different groups of patients such as pancreatic surgery , surgery of stomach and colo-rectum cancer (Gianoti et al, 1999;Wu et al, 2001), critically ill patients (Caparros et al, 2001) and head and neck cancer patients (Van Bokhorst-de van der Schueren et al, 2001).…”
Section: Introductionmentioning
confidence: 99%